The GABBR1 locus and the G1465A variant is not associated with temporal lobe epilepsy preceded by febrile seizures - Sutcliffe James S; Abou-Khalil Bassel; Ma Shaochun; Haines Jonathan L; Hedera Peter (BMC, 2005)
Abstract Background Polymorphism G1465A in the GABBR1 gene has been suggested as a risk factor for non-lesional temporal lobe epilepsy (TLE); however, this genetic association study has not been independently replicated. We attempted to replicate this study in our cohort of patients with TLE. Furthermore, we also analyzed the coding sequence of this gene and searched for disease-causing mutations. Methods We included 120 unrelated individuals with TLE that was preceded by febrile seizures (FS) who did not have any evidence of structural lesions suggesting secondary epilepsy. 66 individuals had positive family history of TLE epilepsy and 54 were sporadic. Each patient was genotyped for the presence of G1465A polymorphism. All exons of the GABBR1 gene were screened by single strand confirmation polymorphism method. Genotypes were compared with two independent matched control groups. Results We detected two A alleles of the G1465A polymorphism in one homozygous control subject (0.87% of all alleles) and one A allele in a patient with TLE (0.45%, not significant). Other detected polymorphisms in coding regions had similar frequencies in epilepsy patients and control groups. No disease causing mutations in the GABBR1 gene were detected in patients with sporadic or familial TLE. Conclusion Our results indicate that TLE preceded by FS is not associated with the polymorphisms or mutations in the GABBR1 gene, including the G1465A polymorphism. The proportion of TLE patients with FS in the original study, reporting this positive association, did not differ between allele A negative and positive cases. Thus, our failure to reproduce this result is likely applicable to all non-lesional TLE epilepsies.